RIVER GOMTI'S ICHTHYOFAUNA BIODIVERSITY, THREAT STATUS, AND CONSERVATION PRIORITY - Dr. Shailendra Kumar Singh, (International Journal of Innovations in Engineering Research and Technology, 2015)
Life cycle features are intimately linked to the food habits of a particular person. Depending on the quantity and kind of food they choose, fish may develop, reproduce, survive, and play an important part in the aquatic ecology. Feeding rivalry among fishes is one consequence of fishes' preference for fish over other common foods. Gut content analysis was used to establish the diets of carp and catfish in this research. Interspecific and intraspecific competition is evident in the fish species' diets based on the wide range of food items they consume. However, it was shown that carp and catfish fishes may be capable of adapting to an omnivorous diet despite preferring phytoplankton over zooplankton and other prey.